PENGUATAN PERILAKU GAYA HIDUP SEHAT DAN RAMAH LINGKUNGAN PADA MASYARAKAT DESA KRAGAN - Rusdiyana, Eksa; Christiano, Gerald; Segoro, Mahesa Ardhaseno; Rahmawati, Mei Maulida; Salsabilla, Salsabilla; Fauziah, Widad Nur (Biro Administrasi dan Akademik, 2025)
The potential of a beautiful village is often not maximized with a beautiful and healthy environmental arrangement. This leads to a slum-like impression, poor sanitation, and affects the health of the village residents. Community service activities through KKN Group 341 UNS raised the theme of K5 Application (Cleanliness, Security, Order, Beauty, and Kinship) and Environmental Preservation in Kragan Village Area, Gondangrejo Kec. Gondangrejo, Karanganyar Regency aims to improve clean and healthy living habits, implement the K5 program, and improve waste management to preserve the environment. The method of implementing activities is carried out through KKN activities with the stages of implementation including; (1) problem identification, (2) determination of objectives, (3) program socialization, (4) implementation of work programs, and (5) evaluation of activity results. Work programs that were successfully implemented included; (1) K5 socialization, (2) socialization and procurement of waste sorting bins, (3) making ecoprint shopping bags, (4) socialization of clean and healthy lifestyles (PHBS), (5) Bulak Hamlet mountain fall, and (6) monitoring the implementation of improving the quality of uninhabitable houses (RTLH). In implementing the program, the community actively participated and the Kragan Village Government fully supported the KKN activities, so that the KKN work program could achieve the expected goals.